Density effect and optimum density of the urban population in China. (May 2017) - Su, Hongjian; Wei, Houkai; Zhao, Jian
This article examines the density effect and the optimum density of the urban population using panel data from China's 284 cities from 2006 to 2010. Considering the endogeneity problem from the employment density in the density effect, we employ the density of the public transport passenger volume instead, and we control the size effect and the structure effect to obtain more reasonable results. Our results indicate that, using the dependent variables of product per labour and wage, the density effect shows an inverted U shape. Further study shows that the optimum urban population density gauged by the total urban population divided by the built-up area is approximately 13, 000 people per km 2 for the prefecture-level cities in China. The results are robust. Based on the concept and value of the optimum urban population density, China has a huge potential urban land use capacity of approximately 28% of total built-up area. China's expansion of the city built-up area and the process of population urbanisation should be coordinated by the optimum urban population density.